Understanding societal approval of the fishing industry and the influence of third‐party sustainability certification. Issue 6 (27th June 2021) - Robinson, Lucy M.; van Putten, Ingrid; Cavve, Blake S.; Longo, Catherine; Watson, Matt; Bellchambers, Lynda; Fisher, Emily; Boschetti, Fabio
Abstract: Commercial fisheries are increasingly interested in greater social acceptance of their operations and practices. For harvesters, achieving acceptance is complex because expectations arise from many societal groups who can differ greatly in their perceptions. Historically, third‐party certification programmes assisted industry in gaining market acceptance (from consumer and investor groups) by improving the ecological sustainability of fishing practices. This focus is diversifying as societal expectations expand beyond ecological concerns to encompass, for instance, equal access and fair distribution of benefits as well as fisheries management and ethical aspects. In this study, we draw on theoretical work from the social acceptance and social licence literature to create a conceptual model that includes eight variables, representing different aspects of societal approval of fisheries. We applied this model to examine the influence of third‐party certification on societal approval of fisheries in Western Australia (WA). Based on study respondents' perceptions, third‐party certification had a statistically significant influence on facilitating government and regulatory approval of industry. Most respondents perceived certification to facilitate industry acceptance from stakeholders, but this was less so for the local community and general public. Contrary to expectations, but perhaps specific to WA because seafood is mostly sold without the ecolabel, certification was less influential on domestic and export market acceptance. Our findings, in WA, highlight certification was not equally influential on all societal approval aspects. Additionally, the conceptual model is sufficiently flexible to assist other fisheries (and industries) in understanding the influence of certification (and other factors) on different societal approval aspects.